Ultra-High Dose Rate FLASH Irradiation Induced Radio-Resistance of Normal Fibroblast Cells Can Be Enhanced by Hypoxia and Mitochondrial Dysfunction Resulting From Loss of Cytochrome C - Han, Jintao; Mei, Zhusong; Lu, Chunyang; Qian, Jing; Liang, Yulan; Sun, Xiaoyi; Pan, Zhuo; Kong, Defeng; Xu, Shirui; Liu, Zhipeng; Gao, Ying; Qi, Guijun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Ultra-high dose rate FLASH irradiation (FLASH-IR) has got extensive attention since it may provide better protection on normal tissues while maintain tumor killing effect compared with conventional dose rate irradiation. The FLASH-IR induced protection effect on normal tissues is exhibited as radio-resistance of the irradiated normal cells, and is suggested to be related to oxygen depletion. However, the detailed cell death profile and pathways are still unclear. Presently normal mouse embryonic fibroblast cells were FLASH irradiated (~ 109 Gy/s) at the dose of ~10-40 Gy in hypoxic and normoxic condition, with ultra-fast laser-generated particles. The early apoptosis, late apoptosis and necrosis of cells were detected and analyzed at 6 h, 12 h and 24 h post FLASH-IR. The results showed that FLASH-IR induced significant early apoptosis, late apoptosis and necrosis in normal fibroblast cells, and the apoptosis level increased with time, in either hypoxic or normoxic conditions. In addition, the proportion of early apoptosis, late apoptosis and necrosis were significantly lower in hypoxia than that of normoxia, indicating that radio-resistance of normal fibroblast cells under FLASH-IR can be enhanced by hypoxia. To further investigate the apoptosis related profile and potential pathways, mitochondria dysfunction cells resulting from loss of cytochrome c (cyt c-/-) were also irradiated. The results showed that compared with irradiated normal cells (cyt c+/+), the late apoptosis and necrosis but not early apoptosis proportions of irradiated cyt c-/- cells were significant decreased in both hypoxia and normoxia, indicating mitochondrial dysfunction increased radio-resistance of FLASH irradiated cells. Taken together, to our limited knowledge, this is the first report shedding light on the death profile and pathway of normal and cyt c-/- cells under FLASH-IR in hypoxic and normoxic circumstances, which might help us improve the understanding of the FLASH-IR induced protection effect in normal cells, and thus might potentially help to optimize the future clinical FLASH treatment.